Dampak Pendidikan Kristen dalam Pembentukan Identitas Keagamaan Anak di Era Digital : Tantangan dan Peluang - Karsa Krisman Gulo; Noverlina Zendrato; Ferdi Eka Darma; Semuel Linggi Topayung (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2024)
Cultural shifts driven by digital technology have significantly influenced educational processes, including Christian education. First, children in the digital era are exposed to various religious perspectives through digital media, which can affect the formation of their religious identity. Second, the role of Christian education in shaping religious identity has become increasingly complex amid the pluralistic and sometimes contradictory flow of information. This study aims to explore the impact of Christian education on the formation of children's religious identity in the digital era, as well as to identify the emerging challenges and opportunities. Employing a qualitative research method based on case studies and digital media content analysis, this research offers a novel perspective on the effectiveness of Christian educational approaches in the modern context. The findings indicate that Christian education still holds a strong potential in shaping religious identity, but it requires adaptive educational strategies that are more relevant to digital dynamics. The holistic conclusion emphasizes the importance of integrating technology in Christian education to strengthen children's religious identity in the digital era.